DI ANTARA UGATAMEE DAN INJIL: TRANSFORMASI TEOLOGI-TEOLOGI PRIBUMI DI TANAH PAPUA - I Ngurah Suryawan (Islam Realitas: Journal of Islamic and Social Studies, 2016)
This article discusses the oral tradition in the form of indigenous theologies that are believed by many communities in Papua about their God as a life savior. Historically, The indigenous theology has an important role in the formation of knowledge about religion, customs, and culture that become orientation of their lives. Indigenous theologies in Papua is experiencing a transformation as the presence of religion. Tensions between indigenous theology and values of the gospel of Christianity particularly give serious impact on the religious orientation of the overall culture of the society. This article explore some teachings of indigenous theology, including the Ugatamee, Hai and Koreri along with their oral traditions and transformations that happened. Artikel ini mendiskusikan tradisi lisan berupa teologi-teologi pribumi yang diyakini oleh berbagai komunitas di tanah Papua tentang Tuhan mereka sebagai penyelamat kehidupan. Teologi pribumi tersebut dalam sejarahnya berperan penting dalam pembentukan pengetahuan tentang religi, adat, dan budaya yang menjadi orientasi kehidupan mereka. Teologi-teologi pribumi yang ada di tanah Papua mengalamai transformasi saat hadirnya agama. Ketegangan antara teologi pribumi dan nilai-nilai injil dalam agama Kristen khususnya berdampak serius terhadap orientasi religi sekaligus budaya masyarakat. Artikel ini mendalami beberapa ajaran teologi pribumi, diantaranya adalah Ugatamee, Hai dan Koreri beserta tradisi-tradisi lisannya dan transformasi-transformasi yang dialaminya.